Precipitation on stacking faults in Mg–9.8wt%Sn alloy. (15th May 2020) - Liu, C.Q.; He, C.; Chen, H.W.; Nie, J.F.
Abstract: In this work, we have systematically investigated precipitation of β′-Mg3 Sn phase on intrinsic stacking faults I1 and I2 in a Mg–9.8 wt%Sn alloy using aberration-corrected scanning transmission electron microscopy. All observed I1 faults are generated by the dissociation of c + a perfect dislocations and bounded by Frank partial dislocations having a Shockley component. Precipitation of β′ on I1 involves a shear of 1/3 < 01 1 ¯ 0>α, similar to its formation directly from the α-Mg matrix. The β′ phase often nucleates at one end of an I1 fault due to the interaction between shear strain fields of β′ and the Shockley component of the Frank partial at that end, and subsequently grows towards the other end of the fault. When the β′ reaches to the other end, the Shockley partial bounding the lengthening end of the β′ reacts with the Frank partial bounding the fault, generating an a perfect dislocation that can glide away from the precipitate and the fault. The observed I2 faults are generated by the dissociation of a perfect dislocations and bounded by Shockley partials. Precipitation of β′ on I2 does not need a shear of 1/3 < 01 1 - 0>α, since the pre-existing I2 fault already provides an ABCA four-layer structure of β′. Thickening of the β′ that has already formed on the I2 involves the successive occurrence of three crystallographically equivalent shears of 1/3 < 01 1 - 0>α on every second (0002)α plane of the α-Mg matrix. Although this thickening mechanism is similar to that of the β′ formed directly from the α-Mg matrix, an a perfect dislocation will be produced when the β′ is thickened to eight layers, and it can again glide away from the precipitate and the fault.